The Ordered Weighted Average Sector Liquid Return Index: A Method for Determining Financial Recovery from Sectoral Debt - Salvador Linares-Mustarós; Maria Àngels Farreras-Noguer; Joan Carles Ferrer-Comalat; José M. Merigó (Mathematics, 2023)
The primary aim of this article is to demonstrate that using the average of ratios as a representative value for measuring the health of a sector does not constitute a valid procedure. After mathematically demonstrating this objective, the article will then focus on introducing a new index for estimating the potential debt return value for a sector or group of companies. Next, the article details the start of the process for creating a new index to improve investors’ understanding of the risk associated with a sector or a group of companies meeting short-term obligations based on assigned probabilities of future sales. Given that said value is intended to represent an indicator of expected liquid solvency, its construction will take treasury tensions into account. An Ordered Weighted Average type of aggregation function is used to aggregate the magnitudes in this scenario. Consequently, the second objective of the present work is the creation of this index, which provides an initial estimate of how much money can be recovered from a sector’s debt.